Em construção... E desconstrução...: discursos e representações presentes nos jornais O Estado de S. Paulo e O Globo durante o governo Castelo Branco (1964-1967) - Forattini, Fernando Miramontes (2018)
With this research, we intend to demystify the Castelo Branco government (1964-1967) and its relationship with the mainstream media by analyzing the editorials and cartoons in the newspapers O Estado de S. Paulo (OESP) and O Globo (OG) – as well as to try to deconstruct the Memory that these newspapers seek to build today about the Castelo government and their participation in it and in the coup. The analysis of journalistic discourses - following Michel Foucault in which discourse is a culturally constructed representation of reality, inserted in a power dispute system - of this period will allow us to question our sources about the supposed social consensus of these press organs during this time frame. This research will therefore study this period as a whole, questioning its legal basis, and other themes such as torture, corruption, political organization, and etc., by using the discourses and representations of these newspapers as an instrument for the dissection of these themes, as well as the source itself. We will do this by asking questions such as how they dealt with their liberal rhetoric in an authoritarian government; what were the trajectories undertaken by both newspapers in their support and criticism; what are the changes in positions and their motives; and how, being the media an important factor in deciding the political-economic agenda and forming opinions, they sought to influence the actions of government or part of civil society. So these newspaper, two of the most important and influential of the time, though extremely different in many aspects, will be the basis for not only understanding them as a source, but also as participants in the events and as social actors, allowing us to understand the period itself in further study